On the phase model in the syntax - Mecner, Paweł (Glottodidactica, 2018)
The article examines some aspects of the modern syntax and algorithmic modeling. In 1974, in Dedham, Massachusetts, an international meeting took place which paved the way for the interdisciplinary research field of biolinguistics. The key focus area was syntax, its hierarchical structure and system of discrete infinity, unusual for the biological world. Here, some aspects of computational efficiency are analyzed in recent generative frameworks: operation Merge, the probe-goal system and the concept of the phase, among others. The aim of this article is to investigate an intriguing structure with final subject of unaccusatives in Yiddish, a Germanic language with Slavonic influences, and to show phase structures, feature inheritance, probe-goal, and a cyclic transfer system.